Efficacy and safety of pharmacological interventions for managing sickle cell disease in children and adolescents: protocol for a systematic review with network meta-analysis - Joana Ferreira; Miguel Brito; Fernando Fernandez-Llimos; Fernanda S Tonin; Catarina Ginete; Mariana Delgadinho (BMJ Open)
Introduction Sickle cell disease (SCD), an inherited haemoglobinopathy, has important impact on morbidity and mortality, especially in paediatrics. Previous systematic reviews are limited to adult patients or focused only on few therapies. We aim to synthesise the evidence on efficacy and safety of pharmacological interventions for managing SCD in children and adolescents.Methods and analysis This systematic review protocol is available at Open Science Framework (doi:10.17605/OSF.IO/CWAE9). We will follow international recommendations on conduction and report of systematic reviews and meta-analyses. Searches will be conducted in PubMed, Scopus and Web of Science (no language nor time restrictions) (first pilot searches performed in May 2022). We will include randomised controlled trials comparing the effects of disease-modifying agents in patients with SCD under 18 years old. Outcomes of interest will include: vaso-occlusive crisis, haemoglobin levels, chest syndrome, stroke, overall survival and adverse events. We will provide a narrative synthesis of the findings, and whenever possible, results will be pooled by means of pairwise or Bayesian network meta-analyses with surface under the cumulative ranking curve analyses. Different statistical methods and models will be tested. Dichotomous outcomes will be reported as OR, risk ratio or HR, while continuous data will be reported as standard mean differences, both with 95% CI/credibility interval. The methodological quality of the trials will be evaluated using the Risk of Bias 2.0 tool, and the certainty of the evidence will be assessed with the Grading of Recommendations Assessment, Development and Evaluation approach.Ethics and dissemination This study refers to a systematic review, so no ethics approval is necessary. We intent to publish our findings in international, peer-reviewed journal. Data will also be presented to peers in scientific events. Additionally, the results obtained in this study may contribute towards the update of therapeutic guidelines and for the development of health policies for SCD.PROSPERO registration number CRD42022328471.